Analisis Pengaruh Kualitas Website Shopee Terhadap Kepuasan Pengguna Berdasarkan Metode WebQual 4.0 (Studi Kasus : Mahasiswa Pengguna Shopee di Universitas Diponegoro) - M. Risqi Amirul Adieb; Aris Sugiharto; Satriyo Adhy (Department of Informatics, Universitas Diponegoro, 2024)
The proliferation of e-commerce business actors creates fierce online buying and selling competition therefore e-commerce needs to maintain its existence. One of the main factors that encourage customers to conduct e-commerce transactions is the user satisfaction level in website acceptance of the e-commerce website's service quality. This research purposes to analyse the quality factors of the Shopee website that influence the level of user satisfaction based on the WebQual 4.0 method and the additional variable of user satisfaction. The results of data analysis and research obtained that the contribution of the influence provided by the WebQual 4.0 dimensions simultaneously on user satisfaction in the acceptance of the Shopee website is 76,2%, in terms of the WebQual 4.0 dimensions simultaneously with a significant influence on user satisfaction, usability that positively and significantly influences user satisfaction, information quality which positively and significantly influences user satisfaction, and service interaction quality with a positive and significant influence on user satisfaction.